Desenvolvimento, projeto, construção e teste de um cilindro de reparo por atrito portátil - Hwang, Henry Fong (2010)
Wave loads introduce significant dynamic stresses on welded connections of offshore structures, leading to fatigue crack growth. Innovations in repair techniques are being pursued to perform these repairs without the need of shutdown of FPSOs (Floating Production Storage and Offloading). While common repair techniques are based on fusion welding process, solid state welding technique such as friction welding has always being sought as an alternative method for repair. The Friction Hydro Pillar Processing (FHPP) technique can be described as a fill and drill process, where a consumable rod is rotated, then entered co-axially into a cavity. Since the repair occurs below the melting point of the material, the process does not suffer from the common welding problems such as cracking, porosity, gas adsorption, atmospheric contamination and hydrogen embrittlement. Looking forward to applying this technology, the company Petrobras signed an agreement with the Federal University of Uberlandia - Brazil, and a FHPP equipment was developed. It was used to optimize the parameters and geometries for the new technique. Later, studies for field application began towards designing a portable friction welding head, which is the mechanical part that applies axial load and rotation to the consumable rod. In the present work, a portable friction welding head was conceived, designed and assembled for operations of 40 kN of axial load and 5.000 rpm. A 15 kg welding head was connected to the equipment. FHPP and FPPW (Friction Pull Plug Welding) tests were performed. Specific chucks and clamping systems for pipes and flat surfaces were developed and tested. The weld head was portablelized and demonstrated itself capable to perform field operations.